Intersession reliability of the interpolated twitch technique applied during isometric, concentric, and eccentric actions of the human knee extensor muscles. Issue 2 (12th April 2017) - Behrens, Martin; Husmann, Florian; Gube, Martin; Felser, Sabine; Weippert, Matthias; Bruhn, Sven; Zschorlich, Volker; Mau‐Moeller, Anett
Abstract: Introduction : Although it has been shown that voluntary activation (%VA) of the knee extensors during isometric contractions can be reliably assessed with the interpolated twitch technique, little is known about the reliability of %VA during concentric and eccentric muscle actions. Therefore, relative and absolute intersession reliability of quadriceps muscle's %VA during different contraction modes was determined. Methods : After a familiarization session, 21 participants (17 males, 25 ± 2 yrs) completed two testing sessions. Paired supramaximal electrical stimuli were administered to the femoral nerve during isometric, concentric, eccentric MVCs, and at rest to assess %VA (stimuli were applied at 70° knee flexion). Results and discussion : Data indicate that %VA of the knee extensors can be reliably measured during isometric [intraclass correlation coefficient (ICC) = 0.89, coefficient of variation (CV) = 4.1%], concentric (ICC = 0.87, CV = 6.6%), and eccentric muscle actions (ICC = 0.86, CV = 7.0%). Muscle Nerve 56 : 324–327, 2017